Evaluation of reverse supply chain strategies for end-of-life EV batteries in Vietnam using AHP–TOPSIS - Viet Khai Le; The Anh Le; Quoc Bay Le; Minh Phuong Thai; Nguyen Phuong Lien Le (Journal of Emerging Science and Engineering, 2026)
The booming development of electric vehicle (EV) adoption in Vietnam has worsened the problem of end-of-life EV battery management in a sustainable and economically feasible way. Reverse supply chain management (RSCM) plays a critical role in reducing environmental risks, resource dependency, and circular economy goals. However, the choice of suitable reverse supply chain strategies is impaired by several economic, environmental, technical, and policy-related barriers. This study proposes an integrated AHP-TOPSIS framework for the evaluation and prioritization of reverse supply chain alternatives for EV batteries in the Vietnamese context. Ten key barriers were identified, from an extensive literature review and expert consultation by twelve domain specialists. High collection and transportation costs (weight = 0.244) and high recycling and processing expenses (weight = 0.162) were shown to be the most significant barriers when AHP was applied to determine their relative importance. The four options—Direct Recycling, Second-Life Applications, Centralized Recycling, and Decentralized/Hybrid Recycling—were then ranked using TOPSIS. According to the findings, Decentralized/Hybrid Recycling had the highest closeness coefficient, followed by Second-Life Applications, while Direct Recycling had the lowest. The results show how adaptable and localized reverse supply chain topologies can help solve the issue of cost-related barriers. In order to promote sustainable EV battery management in Vietnam, the suggested framework provides policymakers and industry stakeholders with useful insights.